Gay and lesbian literature disrupting the heteronormative space of the high school english classroom - Helmer, Kirsten (Sex Education: Sexuality, Society and Learning, 2016)
This paper offers insights into how the teaching of queer topics in English language arts classes can be reframed by bridging the goals, practices and conceptual tools of queer theory to literacy teaching. Drawing on an ethnographic classroom study, which explored a 13-week high school Gay and Lesbian Literature course, this paper discusses how teaching an English literature curriculum centred on the voices and stories of LGBTQI people constitutes a meaningful site for learning and teaching. In the process, I show how a queer-themed literature curriculum not only intervenes disruptively into the heteronormative space of school through its content but also through pedagogical practices that open up new lines of thinking for understanding diverse sexualities and genders. Through vignettes from the classroom, I illustrate how queer moments were enacted in this high school course as the class (a) deconstructed literary and media texts; (b) used moments of discomfort for learning; (c) produced counter-narratives through creative acts; and (d) engaged in experiential learning activities that troubled commonsense understandings of sexuality, sex and gender. The paper aims to provide educators and administrators with ideas on how a comprehensive queer-inclusive English literature curriculum can be implemented in high schools.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; genre; identités LGBTQIA2+; pédagogie; périodes historiques; queer; régions géographiques; sexualité; thématiques; école secondaire; états-unis

"Everyone needs a class like this": High school students' perspectives on a gay and lesbian literature course - Helmer, Kirsten (Educational Forum, 2015)
This article offers insights on how students experienced and made sense of their learning in a trimester-long high school Gay and Lesbian Literature course. Drawing on questionnaires and interviews that the students completed as part of a larger ethnographic study of this class, the author shows how a queer-themed literature curriculum is relevant for both LGBTQ-identifying and straight-identifying students and contributes to a better school climate.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; discipline; identités LGBTQIA2+; pédagogie; périodes historiques; ressource en ligne; régions géographiques; science de l'éducation; thématiques; école secondaire; états-unis